Democratic design experiments in urban planning – navigational practices and compositionist design. Issue 4 (2nd October 2017) - Munthe-Kaas, Peter; Hoffmann, Birgitte
Abstract: In the field of urban planning, public participation and inclusion of citizens have been practised and researched for many years. However, a focus on co-creative urban planning practices seems to have gained more focus over the last decade and calls for new urban planning practices, which allow experimentation and imagination, and at the same time take its outset in the existing networks in the city (such as visions, strategies, regulations and practices) when planning for the future. In this article, we investigate how a compositionist design programme can be translated into the practices of urban planners. We find that the notion of 'democratic design experiments' in many ways meet the demands of the increasingly complex field of urban planning and set out to explore how such a design programme can be applied in practice. We suggest 'navigational practice' as a way of describing how urban planners deal with 'drawing things together' in urban space and introduce 'sensitivity', 'staging' and 'mobilization' as interconnected elements of this practice. We exemplify the significance of these navigational practices by analysing two democratic design experiments in the area of urban waste management in Copenhagen. The article concludes that compositionist design is a powerful contribution to the framing of urban planning projects and that navigational practice can be a productive way of operationalising democratic design experiments in the urban context.